(untitled) (Acta Scientiarum. Biological Sciences, 2013)
The objective of this work was to evaluate the cytotoxic effect of the food dyes erythrosine, brilliant blue and red 40 on the cell cycle of Allium cepa L. Each dye was evaluated at doses of 0.4 and 4.0 ml, at exposure times of 24 and 48 hours, in onion root tip cells. Cells and the presence of chromosomal aberrations were analyzed throughout the whole cell cycle, totaling 5,000 cells for each group of bulbs. The mitotic index was calculated and the statistical analysis was conducted through the Chi-square test (p < 0.05). From the obtained results, it was verified that the food additives erythrosine and brilliant blue were not cytotoxic to the cells of the test system. However, the red 40 dye, at the two evaluated doses and the two exposure times used in this bioassay have promoted a significant reduction in cell division and induced the emergence of anaphasic and telophasic bridge aberrations and micronucleated cells. Additional cytotoxicity studies should be conducted to add information to these and other previously obtained results in order to evaluate, with property, the action of these three dyes on a cellular level.